Repercussões da pandemia de Covid-19 na subjetividade de técnicas de Enfermagem em processo de aposentadoria - SOUSA, Luiza Mariana de (2022)
The contemporary capitalist society overvalues work and devalue its absence. Therefore, it is possible to think that retirement process may cause many repercussions on workers’ subjective. Expatiating about this process as something complex, multifacturial, as well as crossing by history context, social, economic and cultural. Based on that, there is an understanding that the new reality occasioned by Covid-19 pandemic might be considered as a decisive factor on worker’s choice if they keep working or retiring from their jobs. This research aimed to analyze the repercussions of Covid-19 on female Nurse technicians’ subjective during their retirement process. It has as its specific objectives to investigate the meaning of work and retirement process to female Nurse technicians; identify the elements whose work out as source of suffering and pleasure at work and detect the coping strategies used by female Nurse technicians in order to face the changes caused by Covid-19 pandemic and how this new context influences on retirement process. It has as theoretical and methodological basis the conceptual approach of Psychodynamics of work as well as linking with the sócio-historical approach based on dialectical and historical materialism, considering the historicity of individuals who are modified and modifiers of their own social reality. Moreover, it is also characterized as a qualitative study, which utilized sociodemographic questionnaire and conducted a semi-structured interview designed to collect the data with the female Nurse technicians during their retirement process. The analysis of the data was done by critical discourse analysis developed by Fairclough. The contributions of this research was provided through theoretical prodution about retirement process which allow the workers to develop the best coping strategies to handle this process.